PENGARUH FREKUENSI MEDIA DAN KETERPAPARAN INFORMASI TENTANG KB TERHADAP PERSEPSI JUMLAH ANAK IDEAL: ANALISIS DATA SDKI 2017 - Muhammad Ancha Sitorus; Putra Apriadi Siregar (Jurnal Kesehatan, 2021)
The National Population and Family Planning Board of North Sumatra Province continue to socialize the ideal number of children in a family of 2, but the TFR is still high at 2.9. Information about the Family Planning (KB) program expected to change people's thinking patterns about the number of children. Ideal. The research objective was the influence of media frequency and exposure to information about kb on the perception of the ideal number of children. This study is a further analysis of the 2017 IDHS using a cross-sectional. The population in this study were all women of childbearing age 15-49 years. The sample in this study was 2300 WUS — bivariate analysis using cross-tabulation and chi-square test. The results of this study indicate that the respondents who stated the ideal child were 1-2 people as many as 48% while 52% stated that the ideal child was ≥ three people. There is a relationship between the frequency of reading newspapers (p = 0.01), listening to the radio (p = 0.028), watching TV (P <0.001), using the internet (P <0.001), reading exposure to family planning programs in newspapers (0.001), the radio (0.005), exposure to seeing family planning programs on TV (0.001) with the ideal number of children. The National Population and Family Planning Board of North Sumatra Province must be able to choose effective information media to increase public perceptions about the ideal number of children, such as urban communities better use radio and internet media and rural communities use newspaper information media.